PENERAPAN MODEL PEMBELAJARAN PJBL-STEM PADA ALAT PEMBAKARAN SAMPAH TANPA ASAP MATERI SUHU, KALOR, DAN PEMUAIAN UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS VII SMPN 1 TAPUNG HULU - Yola Aprila (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
The study aims to determine the cognitive abilities of class VII students through the application of the STEM-based PjBL model using smokeless waste incinerator media and to determine the differences in cognitive abilities of classes that use the PjBL-STEM model with conventional learning. This study was conducted at SMPN 1 Tapung Hulu, Kampar Regency, Riau Province. The type of research used is Quasi Experimental Design with the Posttest Only Non-Equivalent Control Group Design method. The population of this study was 176 students. The sample in this study was 59 students, with class VII D consisting of 29 students as the experimental class and class VII A consisting of 30 students as the control class. The data collection instrument was in the form of a cognitive ability posttest consisting of 15 multiple choice questions. The data analysis technique used was descriptive analysis through the average value of student learning outcomes and inferential analysis through normality tests, homogeneity tests and hypothesis tests. The results of the descriptive analysis can be concluded by using the PjBL-STEM model on smokeless waste burners better than the control class. The results of the inferential analysis of the Hypothesis Test in this study using the independent sample T-test showed that there was a significant difference between the cognitive abilities of students. Therefore, the STEM-based PjBL models using smokeless waste burner media can be used as an alternative that can be applied in the science learning process in schools to improve students' cognitive learning outcomes.